Gambaran Kecemasan Siswa dan Kesulitan Materi Fisika pada Asesemen Sumatif Semester Ganjil - Lisa Sutami Suharlan (Universitas Nusa Cendana, 2026)
This study aimed to describe students’ anxiety levels and their perceptions of difficulties in physics materials when facing the odd semester summative assessment. The study employed a descriptive quantitative approach involving 24 students as research subjects. Data were collected through anxiety questionnaires and identification of physics topics perceived as difficult by students. The results showed that most students were in the moderate anxiety category, with 21 students classified as moderate anxiety and 3 students classified as high anxiety, while no students were found in the low anxiety category. The physics topics most commonly perceived as difficult were free- fall motion and circular motion in kinematics. Students reported that these difficulties were mainly caused by limited formula mastery and difficulties in interpreting problems. Overall, the findings indicate that most students experienced a moderate level of anxiety in facing physics assessments, accompanied by perceptions of difficulty in several kinematics topics